A case control study on infant massage and breastfeeding outcome among mothers - Chan, Kim Geok; Saloma, Pawi; Lee, WF; Ooi, Chor Yau; Zurraini, Arabi; Helmy, Hazmi (The Malaysian Family Physician Journal Academy of Family Physicians of Malaysia, 2019)
Introduction: The practice of infant massage has been reported to provide benefits of improved mother-infant interaction and breastfeeding outcome. The objective of the study is to examine the influence of infant massage on breastfeeding outcome. Methods: Using a comparative cohort study design, 310 mothers whose babies were 4 weeks old and still breastfeeding were recruited from the selected MCH clinics within Kuching District for the intervention and control groups, after prior ethnics’ approval. Study group mothers (mean age 29.2 years) were taught the adapted infant massage program by a certified infant massage instructor in a small group of 4-5 mothers each. A bottle of (60 mls) cold-pressed olive oil and a hand-out of the massage strokes were given to mothers who were asked to have baby massage session twice a day for 10-15 minutes each. Questionnaire on breast feeding related outcome (frequency, duration, supplementary food; exclusiveness) were administered to both groups of mothers on recruitment and on baby’s age 12 weeks. A dropout of 10 study group participants was noted due to loss to contact. Results: 84.8% (n=123) of the study group (N=145) reported still breastfeeding versus 77.4% (n=120) in the control group (N=155). However, almost half of the both groups had started on complementary feeding with formula milk of at least 1-2 times per day. Higher percentage of the study group then control group breastfed their babies at least 3-4 times per day. Apparently more of the study group reported at least 6-10 minutes for each breastfeeding session. Among the reasons indicated from mothers of both groups for not breastfeeding include milk insufficiency and the needs to resume work. Conclusion: Infant massage could be one of the factors which influence positively on breastfeeding outcome in the local context.